Social Media Analysis: CGIAR Climate Security Observatory - Carneiro, Bia; Resce, Giuliano; Ruscica, Giosuè; Simone, Daniele di (2023)
The Climate Security Observatory (CSO) is an online platform for stakeholder decision-making that provides access to a range of global analyses related to climate and security. The CSO is based on an integrated climate security framework that helps understand the complexity of the climate-security interface. As part of the CSO Methods Paper Series, this report details the method used for the social media analysis.